Balassa-Samuelson, product differentiation and transition - Richard Frensch (Osteuropa-Institut München, 2006)
Recent panel studies have found relatively high estimates for the elasticity of real exchange rates with respect to productivity measures in transition economies within Balassa- Samuelson frameworks. This contrasts with other findings reporting cross-section price-income elasticity estimates to depend positively on average income in the sample. This paper aims to reconcile both results by putting real exchange rate developments of transition economies in an international perspective. We illustrate the special status of these economies in a simple world-wide Balassa-Samuelson-type price-income benchmark relationship between a real exchange rate measure (Penn World Table comparative prices, i.e., exchange rate gaps) and PPP-adjusted per capita income. A pronounced undervaluation at the start of transition, followed by a strong appreciation results in normalisation towards the benchmark for Central and East European economies (CEEC) but not for the CIS. We then make an attempt at extending the simple price-income relationship to incorporate other real factors as well as reforms related to price deregulation. Our results imply that, when accounting for demand shifts, external liberalisation, and especially for reform effort, the price-income-elasticity for CEEC economies was not different from that of non-transition economies during the nineties.
Keywords: F40; F43; 330; Balassa-Samuelson; transition